2017
DOI: 10.1111/ctr.13115
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in critically ill patients: Preoperative predictive factors of post‐transplant mortality to avoid futility

Abstract: Low lactatemia lactate level and the absence of ARDS could be useful criteria in selecting those patients in ICU who could be eligible for liver transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 15 publications
1
52
0
2
Order By: Relevance
“…However, in a more recent study by Michard and colleagues, the presence of SLI as defined by a PaO 2 /FiO 2 < 200 mm Hg significantly affected post‐transplantation survival in patients with both ALF and acute on chronic liver failure (ACLF). On multivariate analysis, they found that pre‐transplant SLI (PaO 2 /FiO 2 < 200 mm Hg) was independently associated with mortality 90‐days post‐LT with a hazard ratio (HR) of 5.9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in a more recent study by Michard and colleagues, the presence of SLI as defined by a PaO 2 /FiO 2 < 200 mm Hg significantly affected post‐transplantation survival in patients with both ALF and acute on chronic liver failure (ACLF). On multivariate analysis, they found that pre‐transplant SLI (PaO 2 /FiO 2 < 200 mm Hg) was independently associated with mortality 90‐days post‐LT with a hazard ratio (HR) of 5.9 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the proportion of patients with ALF and SLI listed for LT was 37.4% compared to 41.9% for patients without SLI. One reason for decreased rates of LT in patients with SLI may be that the poor predicted post‐LT survival leads to concern by the clinician or surgeon prior to surgery . Another reason may be owing to the development of cardiac and in particular right ventricular failure, which may jeopardize the newly implanted liver as a well‐recognized cause of primary graft nonfunction .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with a recent report that identified severe acute respiratory distress syndrome as an independent factor associated with post-transplant mortality. 118 Improvement or stabilization in OFs in the immediate pretransplant period has been associated with favourable post-LT outcomes in patients with ACLF, suggesting that the evolution of OFs should at least be controlled, if not improved, before considering an LT. 98,115 Another important point to consider is the timeframe of LT. In most studies reporting favourable post-LT outcomes in these severely ill patients, an "early" LT has been performed (time between placement on the waiting list and LT ranging from 3-9 days).…”
Section: Therapiesmentioning
confidence: 99%